Gut and urinary microbiota: the causes and potential treatment measures of renal cell carcinoma - Yang, Jian-wei; Wan, Shun; Li, Kun-peng; Chen, Si-Yu; Yang, Li (Frontiers in Immunology, 2023)
Mounting evidence suggests that the gut microbiota plays a crucial role in the development and treatment of various cancers. Recent research on the urinary microbiota challenges the long-standing belief that urine is sterile, as urinary microbiota has been implicated in the development of bladder and prostate cancers, similar to the role of gut microbiota in cancer development. Although the precise involvement of microbiota in the proliferation and differentiation of renal cell carcinoma (RCC) remains unclear, dysbiosis is considered one possible mechanism by which microbiota may contribute to RCC development and treatment. This review summarizes potential mechanisms by which gut microbiota may contribute to the development of RCC, and provides evidence for the involvement of urinary microbiota in RCC. We also explore the role of gut microbiota in RCC treatment and propose that the composition of gut microbiota could serve as a predictive marker for the potential efficacy of immune checkpoint inhibitors (ICIs) in RCC patients. Additionally, evidence suggests that modulating the abundance and distribution of microbiota can enhance the therapeutic effects of drugs, suggesting that microbiota may serve as a promising adjuvant therapy for RCC. Overall, we believe that further investigation into the gut and urinary microbiome of RCC patients could yield valuable insights and strategies for the prevention and personalized treatment of RCC.